2015
DOI: 10.1021/am507854s
|View full text |Cite
|
Sign up to set email alerts
|

pn-Heterojunction Effects of Perylene Tetracarboxylic Diimide Derivatives on Pentacene Field-Effect Transistor

Abstract: We investigated the heterojunction effects of perylene tetracarboxylic diimide (PTCDI) derivatives on the pentacene-based field-effect transistors (FETs). Three PTCDI derivatives with different substituents were deposited onto pentacene layers and served as charge transfer dopants. The deposited PTCDI layer, which had a nominal thickness of a few layers, formed discontinuous patches on the pentacene layers and dramatically enhanced the hole mobility in the pentacene FET. Among the three PTCDI molecules tested,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Perylene diimides (PDIs) are fluorophores with exceptional thermal and photochemical stability and strong absorption in the visible and high fluorescence quantum yields. Due to these properties, PDIs have been used in diverse applications such as light-emitting diodes, , field-effect transistors, , sensing, , and photovoltaic cells. , However, dyads of PDIs with other moieties, namely, transition metal complexes, enlarge the processes of electronic excitation and decay of PDI, broadening the scope of their potential applications. The long-lived triplet state of PDI can be populated via strong spin–orbit coupling induced by heavy metals, as observed in Pt­(II) square planar complexes with PDI covalently linked to the metal center by an acetylide bond. However, in palladium complexes where two Pd centers are attached to PDI by metal–carbon σ bonds, the spin–orbit coupling is very small, and PDI is highly fluorescent …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perylene diimides (PDIs) are fluorophores with exceptional thermal and photochemical stability and strong absorption in the visible and high fluorescence quantum yields. Due to these properties, PDIs have been used in diverse applications such as light-emitting diodes, , field-effect transistors, , sensing, , and photovoltaic cells. , However, dyads of PDIs with other moieties, namely, transition metal complexes, enlarge the processes of electronic excitation and decay of PDI, broadening the scope of their potential applications. The long-lived triplet state of PDI can be populated via strong spin–orbit coupling induced by heavy metals, as observed in Pt­(II) square planar complexes with PDI covalently linked to the metal center by an acetylide bond. However, in palladium complexes where two Pd centers are attached to PDI by metal–carbon σ bonds, the spin–orbit coupling is very small, and PDI is highly fluorescent …”
Section: Introductionmentioning
confidence: 99%
“…Perylene diimides (PDIs) are fluorophores with exceptional thermal and photochemical stability and strong absorption in the visible and high fluorescence quantum yields. 1−4 Due to these properties, PDIs have been used in diverse applications such as light-emitting diodes, 5,6 field-effect transistors, 7,8 sensing, 9,10 and photovoltaic cells. 11,12 However, dyads of PDIs with other moieties, namely, transition metal complexes, enlarge the processes of electronic excitation and decay of PDI, broadening the scope of their potential applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To test the theory afore-described, our photoconductance single-molecule experiments were performed on scanning tunneling microscopy break junctions ,, (STM-BJs) with perylene tetracarboxylic diimide (PTCDI) molecules attached to Au-electrode via Au–amine bonds (Au-NH 2 -PTCDI-NH 2 -Au), depicted in Figure a. PTCDI and its derivatives are known to be highly photoactive, and have been extensively studied in recent years, leading to the fabrication of high-performance optoelectronic devices such as organic light-emitting diodes, solar cells, and photodetectors. We used a monochromator (TLS 25 with spectral range 360 nm to 1000 nm) to apply photon emissions at fixed 495 nm wavelength (corresponding to an energy of 2.5 eV, in resonance with PTCDI’s H–L gap), through an ultrathin (∼600 μm in diameter) fiber optical cable to the single molecular STM-BJs formed in toluene solution while monitoring the electronic current of the junction. Full experimental details are provided in the SI.…”
mentioning
confidence: 99%
“…Specifically, a layer of p-type semiconductor α6T was deposited on top of the F 16 CuPC semiconducting layer and the source/drain electrodes (Figure 5). It has been reported that the use of a pn heterojunction active channel layer in OFETs can realize ambipolar charge transport characteristics and/or improve charge carrier mobility [61][62][63][64][65]. In particular, the V T is a function of the thickness of the top layer in the pn heterojunction [66], which may allow the use of V T as the sensitivity parameter of the OFET temperature sensor in a more controllable manner.…”
Section: Ofet Semiconductor Channel As Sensing Elementmentioning
confidence: 99%